OPTIMALISASI ENERGI PADA POMPA KALI SOLO I - Sonden Winarto (Swara Patra, 2019)
Recent increases in energy prices and electricity tariffs have resulted in increased operating costs and lower sources of income for consumers. Therefore looking for alternatives with energy optimization is an wise action/step/decision that is urgent to be done. Energy optimization is attractive to for the public, especially in industries and commercial buildings, considering that the fraction of energy costs is quite high in the overall operating costs. The potential for energy optimization in most industries ranges from 20 - 40%. Most of this potential can be easily implemented through performance improvements, operating and maintenance procedures do not require investment or with little investment. In the calculation or analysis performed on Pumps of Kali Solo I there is a waste of around 13.4 kW or Rp. 146,016,000, - per year of energy that should be used. If the pump is optimized or improved, then in other words it will get a savings of 37% of the energy used. Keywords: Pumps, Energy, Optimization